Measurement Problems in Decision Analysis - Moore, P. G. (Institutional Knowledge at Singapore Management University, 1973)
Decision analysis is a procedure which has received considerable attention in the management literature in recent years. Attempts to apply the decision theory framework, elegantly developed by Savage, Pratt, Raiffa and Schlaifer and Howard, have only been outstandingly successful in a relatively small number of areas.